1988
DOI: 10.1259/0007-1285-61-729-851
|View full text |Cite
|
Sign up to set email alerts
|

Congenital hemihypertrophy with adrenal adenoma and medullary sponge kidney

Abstract: This is a report of a 10-year-old girl with congenital hemihypertrophy (CH) associated with medullary sponge kidney (MSK) and adrenocortical adenoma. Computed tomography (CT) and ultrasonography demonstrated a small, non-functional, adrenocortical adenoma. A search of the literature failed to reveal any previously reported case having all three conditions. A 10-year-old Japanese girl was admitted with fever, headache and vomiting of 2 days duration. She was born without complications after full-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 14 publications
0
16
2
Order By: Relevance
“…Epidemiological studies of IHH have shown the birth incidence to be 1:86,000 live births [Tomooka et al, 1988]. Females outnumber males two to one [Warkany, 1971], and an increased birth weight has been observed (mean 3.8 kg) [Leisenring et al, 1994].…”
Section: Clinical Characteristics Of Ihhmentioning
confidence: 99%
“…Epidemiological studies of IHH have shown the birth incidence to be 1:86,000 live births [Tomooka et al, 1988]. Females outnumber males two to one [Warkany, 1971], and an increased birth weight has been observed (mean 3.8 kg) [Leisenring et al, 1994].…”
Section: Clinical Characteristics Of Ihhmentioning
confidence: 99%
“…Such syndromes include neurofibromatosis, Klippel-TrenaunayWeber syndrome, McCune-Albright syndrome, and BeckwithWiedemann syndrome (BWS). 1 The incidence of IH is ∼1/86 000 live births, 3 with a male:female ratio of 1:2. 1 The aetiology of IH is unknown.…”
mentioning
confidence: 99%
“…Hemihyperplasia, is a condition in which there may be asymmetrical overgrowth of the face, cranium, trunk, and/or limbs on one side of the body [21,22]. There may be asymmetrical visceromegaly on the ipsilateral or contralateral side [9].…”
Section: Discussionmentioning
confidence: 99%
“…There may be asymmetrical visceromegaly on the ipsilateral or contralateral side [9]. The incidence of IH is ∼1/86 000 live births, [7,23] with a male: female ratio of 1:2 [22] . In the current study, all cases were sporadic and had negative family history with male to female ratio of 1:1.…”
Section: Discussionmentioning
confidence: 99%